WORK LIFE BALANCE GURU DALAM PERSPEKTIF MANAJEMEN SDM PENDIDIKAN DI ERA DIGITAL - Annisa Dwi Asmarani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher work life balance has become an important issue in education because it is closely related to teachers’ well-being, performance, and loyalty. High work demands, administrative burdens, and the development of educational technology have caused teachers to experience difficulties in balancing their personal and professional lives. This study aims to examine teacher work life balance from the perspective of educational human resource management. The study employed a qualitative literature review method by analyzing various relevant national and international scientific journals. Data collection was conducted through the stages of identification, selection, and classification of articles, which were then analyzed using content analysis techniques. The findings indicate that work life balance influences teachers’ job satisfaction, performance, loyalty, and psychological well-being. In addition, work-life balance is affected by both internal and external factors, such as time management skills, workload, work environment, organizational support, and the development of educational technology. From the perspective of educational human resource management, schools play an important role in supporting teacher work life balance through workload management and the creation of a healthy work environment. Therefore, attention to teacher work life balance should become an important part of educational human resource management strategies.